2022
DOI: 10.1002/jcsm.12940
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatinine to cystatin C ratio reflects preoperative and early postoperative walking ability in older patients with hip fracture

Abstract: Background The sarcopenia index (SI), calculated as the ratio of serum creatinine to cystatin C levels, reflects skeletal muscle mass and strength. Patients with hip fracture (HF) and sarcopenia have poor functional outcomes, and many require long‐term care after surgery. We hypothesized that the SI can predict preoperative and early postoperative functional outcomes. Methods Preoperative serum creatinine and cystatin C were measured to calculate the SI for patients with surgically treated HF (n = 130, mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
12
2
Order By: Relevance
“…Sarcopenia is reported to be associated with a risk of atherosclerosis,30–34 CVD9 35–38 and mortality 10–12. Recent studies showed that SI is useful marker for sarcopenia and physical activity levels 13–15 39. In addition, SI is reported to be associated with incident CVD17 18 and mortality 17 40–42.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is reported to be associated with a risk of atherosclerosis,30–34 CVD9 35–38 and mortality 10–12. Recent studies showed that SI is useful marker for sarcopenia and physical activity levels 13–15 39. In addition, SI is reported to be associated with incident CVD17 18 and mortality 17 40–42.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this case report showed that an older patient with bilateral symptomatic incomplete AFFs and severe anterolateral bowing was successfully treated using stainless elastic intramedullary nails. n Naoki Okubo, MD, PhD 1,2 Takashi Yoshida, MD, PhD 1 Kazuya Tanaka, MD 1 Mizuki Asano, MD 1 Taku Nakazawa, MD 1 Masato Ohara, MD 1,2 Kunihiko Hosoi, MD, PhD 1 Kenji Takahashi, MD, PhD 2…”
Section: Discussionmentioning
confidence: 99%
“…Fragility fractures, such as hip and vertebral fractures, have negative impacts on functional outcomes and mortality 1,2 . Treatment of osteoporosis with bone resorption inhibitors resulted in significant benefits in fracture prevention and life expectancy 3 ; however, their long-term use has been associated with atypical fractures 4 .…”
mentioning
confidence: 99%
“…The FIM walk item is scored on a 7-point scale with scores ranging from 1 to 7, with a higher score indicating a higher degree of independence. As described in previous studies, the ‘independent’ group included patients who scored ≥6 points for the FIM walk item, whereas the ‘non-independent’ group included patients who scored ≤5 points for the FIM walk item [9]. The assessments were performed at discharge by the same physical therapist who had supervised the rehabilitation.…”
Section: Methodsmentioning
confidence: 99%
“…It is imperative to understanding the factors influencing postoperative ambulatory function before surgical intervention to establish a comprehensive treatment strategy for postoperative walking independence following HF surgery. Baseline and preoperative clinical factors, such as age [7], preadmission walking independence [8], fracture type [9], operative delay [10], anemia [11] and nutritional status [12], have been reported to be associated with postoperative walking independence in patients with HF. Thus, it is difficult to predict postoperative walking independence in patients with HF using one or two single factors, necessitating the analysis of multiple factors [13].…”
Section: Introductionmentioning
confidence: 99%